Difference between revisions of "008A Sample Final A, Question 11"

From Math Wiki
Jump to navigation Jump to search
(Created page with "'''Question: ''' Decompose into separate partial fractions <math>\frac{3x^2+6x+7}{(x+3)^2(x-1)}</math> {| class="mw-collapsible mw-collapsed" style = "text-align:left;" !Fo...")
 
 
(3 intermediate revisions by the same user not shown)
Line 2: Line 2:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Foundations
+
!Foundations: &nbsp;
 
|-
 
|-
 
|1) How many fractions will this decompose into? What are the denominators?
 
|1) How many fractions will this decompose into? What are the denominators?
Line 10: Line 10:
 
|Answer:
 
|Answer:
 
|-
 
|-
|1) Since each of the factors are linear, and one has multipliclity 2, there will be three denominators. The linear term, x -1, will appear once in the denominator of the decomposition. The other two denominators will be x + 3, and <math>(x + 3)^2</math>.
+
|1) Since each of the factors are linear, and one has multipliclity 2, there will be three denominators. The linear term, <math>x -1</math>, will appear once in the denominator of the decomposition. The other two denominators will be <math>x + 3 \text{, and } (x + 3)^2</math>.
 
|-
 
|-
|2) After writing the equality, <math>\frac{3x^2 +6x + 7}{(x + 3)^2(x - 1)} = \frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>, clear the denominators, and use the cover up method to solve for A, B, and C. After you clear the denominators, the cover up method is to evaluate both sides at x = 1, -3, and any third value. Each evaluation will yield the value of one of the three unknowns.
+
|2) After writing the equality, <math>\frac{3x^2 +6x + 7}{(x + 3)^2(x - 1)} = \frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>, clear the denominators, and evaluate both sides at x = 1, -3, and any third value. Each evaluation will yield the value of one of the three unknowns.
 
|}
 
|}
  
Line 18: Line 18:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 1:
+
!Step 1: &nbsp;
 
|-
 
|-
|From the factored form of the denominator we can observe that there will be three denominators: <math>x - 1, x + 3</math>, and <math>(x + 3)^2</math>. So the final answer will be of the form: <math>\frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>
+
|From the factored form of the denominator we can observe that there will be three denominators: <math>x - 1, x + 3</math>, and <math>(x + 3)^2</math>. So the final answer with have the following form: <math>\frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 2:
+
!Step 2: &nbsp;
 
|-
 
|-
|Now we have the equality <math>\frac{3x^2 +6x + 7}{(x + 3)^2(x - 1)} = \frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>. Now clearing the denominators we end up with <math>A(x + 3)^2 + B(x - 1)(x + 3) + C(x - 1) = 3x^2 + 6x + 7</math>.
+
|Now we have the equality <math>\frac{3x^2 +6x + 7}{(x + 3)^2(x - 1)} = \frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>. We clear the denominators and end up with <math>A(x + 3)^2 + B(x - 1)(x + 3) + C(x - 1) = 3x^2 + 6x + 7</math>.
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 3:
+
!Step 3: &nbsp;
 
|-
 
|-
|To proceed we start by evaluating both sides at different x-values. We start with x = 1, since this will zero out the B and C. This leads to <math>A(1 + 3)^2 = 3(1)^2 + 6(1) + 7</math><math>16A = 3 + 6 + 7</math>, and finally A = 1.
+
|By evaluation both sides by using x = 1, we will zero out the B and C. This leads to <math>A(1 + 3)^2 = 3(1)^2 + 6(1) + 7,  16A = 3 + 6 + 7</math>&nbsp;, and finally <math>A = 1</math>.
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 4:
+
!Step 4: &nbsp;
 
|-
 
|-
|Now evaluate at -3 to zero out both A and B. This yields the following equations <math>C((-3) - 1) = 3(-3)^2 + 6(-3) + 7</math>, <math>-4C = 3(9) - 18 + 7</math>, <math>-4C = 27 - 11</math>, and <math>C = -4</math>
+
|Now evaluating at x = -3 to zero out both A and B. This yields the following equations <math>C((-3) - 1) = 3(-3)^2 + 6(-3) + 7</math>, <math>-4C = 3(9) - 18 + 7</math>, <math>-4C = 27 - 11</math>, and <math>C = -4</math>
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 5:
+
!Step 5: &nbsp;
 
|-
 
|-
|To obtain the value of B we  can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us <math>A(0 + 3)^2 + B(0 - 1)(0 + 3) + C(0 - 1) = 9A -3B -C = 7</math>. However, we know the values of both A and C, which are 1 and -4, respectively. So <math>9 -3B - (-4) = 7</math>, <math>-3B + 13 =  7</math>, <math>-3B = -6</math>, and finally <math>B = 2</math>. This means the final answer is <math>\frac{1}{x - 1} + \frac{2}{x + 3} - \frac{4}{(x + 3)^2}</math>
+
|To obtain the value of B we  can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us <math>A(0 + 3)^2 + B(0 - 1)(0 + 3) + C(0 - 1) = 9A -3B -C = 7</math>. However, we know the values of both A and C, which are 1 and -4, respectively. So <math>9 -3B - (-4) = 7</math>, <math>-3B + 13 =  7</math>, <math>-3B = -6</math>, and finally <math>B = 2</math>.
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Final Answer:
+
!Final Answer: &nbsp;
 
|-
 
|-
 
|<math>\frac{1}{x - 1} + \frac{2}{x + 3} - \frac{4}{(x + 3)^2}</math>
 
|<math>\frac{1}{x - 1} + \frac{2}{x + 3} - \frac{4}{(x + 3)^2}</math>

Latest revision as of 22:58, 25 May 2015

Question: Decompose into separate partial fractions

Foundations:  
1) How many fractions will this decompose into? What are the denominators?
2) How do you solve for the numerators?
Answer:
1) Since each of the factors are linear, and one has multipliclity 2, there will be three denominators. The linear term, , will appear once in the denominator of the decomposition. The other two denominators will be .
2) After writing the equality, , clear the denominators, and evaluate both sides at x = 1, -3, and any third value. Each evaluation will yield the value of one of the three unknowns.

Solution:

Step 1:  
From the factored form of the denominator we can observe that there will be three denominators: , and . So the final answer with have the following form:
Step 2:  
Now we have the equality . We clear the denominators and end up with .
Step 3:  
By evaluation both sides by using x = 1, we will zero out the B and C. This leads to  , and finally .
Step 4:  
Now evaluating at x = -3 to zero out both A and B. This yields the following equations , , , and
Step 5:  
To obtain the value of B we can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us . However, we know the values of both A and C, which are 1 and -4, respectively. So , , , and finally .
Final Answer:  

Return to Sample Exam